Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Preparation and characterization of bioceramic nanocomposites based on hydroxyapatite (HA) and carboxymethyl cellulose (CMC) - Kumar, Annamalai Pratheep; Mohaideen, Kamal Khaja; Alariqi, Sameh A. S.; Singh, Raj Pal (Macromolecular Research, 2010)
We report the synthesis of biomimetic nanocomposites based on carboxymethyl cellulose (CMC) and hydroxyapatite (HA) nanoparticles via a co-precipitation method. Physico-chemical characterization was performed before and after calcination by Fourier transform infrared (FTIR) spectroscopy, solid state (31)P nuclear magnetic resonance (NMR) spectroscopy, and thermogravimetric analysis (TGA). The formation of nanocomposites was observed by wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDX), and transmission electron microscopy (TEM). The spectral and crystallographic data indicated the formation of hydroxyapatite in the presence of CMC. They were observed as aggregates of HA nanoparticles and CMC, whose sizes were approximately similar to 260 +/- 40 nm. The crystallite size of the hydroxyapatite particles decreased (with 2 wt% 18 +/- 3 nm) with increasing CMC content. The morphological aspects of the calcined samples revealed the sintering ability of HA nanoparticles. Nanocomposites of hydroxyapatite nanoparticles that mimic the process of nucleation and growth in nature can be prepared using biomacromolecules such as CMC.
Keywords: biopolymer; cellulose; hydroxyapatite; Nanoparticles; Particle size; X-ray diffraction

Influence of initial particle size on the magnetostriction of sintered cobalt ferrite derived from nanocrystalline powders - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of Magnetism and Magnetic Materials, 2013)
The role of initial particle size on the magnetostriction coefficient of sintered cobalt ferrite derived from nanocrystalline powders is studied. Nanoparticles of cobalt ferrite with different sizes in the range 3-80 nm are synthesized by an autocombustion method using metal nitrates and glycine. It has been observed that the initial particle size of the starting powders has a strong influence on the magnetostrictive behavior of sintered cobalt ferrite. Highest magnetostrictive strain and strain derivative are obtained for sintered ferrite derived from nanoparticles of size < 5 nm. The results show that higher magnetostriction coefficient for sintered cobalt ferrite can be achieved by compacting nanocrystalline particles of very small size. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; magnetic properties; Magnetostriction; Microstructure; Nanocrystalline; Particle size

Carbon dioxide sequestration: influence of porous media on hydrate formation kinetics - Bhattacharjee, Gaurav; Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (ACS Sustainable Chemistry & Engineering, 2015)
In the present study, CO, sequestration by hydrate formation in porous sediments has been discussed. Two siliceous materials with high porosities, pumice and fire hardened red clay (FHRC), have been used as packing materials in a fixed bed setup to study hydrate formation kinetics. The results obtained using the aforementioned materials were compared with those obtained using silica sand and quartz. Carbon dioxide hydrate formation kinetics was studied at 3.0 MPa pressure and 274 K temperature. Two different types of experiments were conducted: (a) using a constant volume of water and (b) maintaining a constant bed height. These experiments were conducted using the different porous media individually as packing materials. It was observed that pumice as the porous medium showed better hydrate formation kinetics resulting in 46 mol % water to hydrate conversion in 5 h. Moreover, kinetics was enhanced with decrease in the bed height of pumice; this suggests that at field scale adaptation of CO, sequestration in geological formations, mass transfer limitations would be significant. The effects of particle size on hydrate formation kinetics were also investigated. It was observed that hydrate formation kinetics was enhanced with decrease in the particle size fraction.
Keywords: Bed height; Gas hydrate; gas uptake; Geological sequestration; Particle size

Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound

Influence of carbon based supports on selectivity behavior of diols and propanol in Ru catalyzed glycerol hydrogenolysis - Mane, Rasika B.; Patil, S.; Shirai, Masayuki; Rayalu, Sadhana S.; Rode, Chandrashekhar V. (Applied Catalysis B: Environmental, 2017)
Activated carbon (AC) and three graphite materials were studied as supports for Ru catalyzed glycerol hydrogenolysis to propanediols and 1-propanol. Structural characteristics of AC and graphite materials were found to greatly affect the reducibility and particle size of supported Ru and hence, the activity and product distribution in glycerol hydrogenolysis. XRD of graphite materials showed distinctly (002) plane having highly organized layered structure and the peak intensity decreased in the order of Ru/KS150 > Ru/HSAG100 > Ru/KS6 due to decrease in the graphite sheet thickness. In Raman, the intense D band in HSAG100 compared to that in KS6 and KS150 samples indicated its highly amorphous nature or mixed carbon hybridization. Glycerol conversion for Ru on AC was higher than that on graphite and among different graphites, it showed a descending activity order of Ru/KS6 > Ru/HSAG100 > Ru/KS150. The product distribution for AC and HSAG100 supported Ru was similar, giving 1-propanol (45%) alongwith 1,2-propanediol (1,2-PDO) (37%) and 1,3-propanediol (1,3-PDO) (9–11%). For graphite supports, availability of Ru although bigger in size (4–5 nm), would be higher on the surface than in case of AC which formed deep hydrogenolysis products like 1-, 2- propanol, ethanol etc.
Keywords: activated carbon; Amorphous carbon; catalysis; Glycerol; Glycerol conversions; Glycerol hydrogenolysis; graphite composites; Graphite supports; Hydrogenolysis; Hydrolysis; layered structures; Particle size; Product distributions; Propanediols; Propanol; Selectivity behavior; Structural characteristics; Structural effect; Structural effects

Effect of rice husk particle size on ZSM-5 physico-chemical properties for selective formation of 1,3,5-trimethyl-2-benzylbenzene (Pharmaceutical Intermediate) - Ghuge, Gorakh; Niphadkar, Prashant; Rathod, Simmy; Bokade, Vijay V. (ChemistrySelect, 2021)
Rice husk, rich in silica and abundantly available as waste, is presently destroyed by burning, which creates environmental issues. Thus, it will be advantageous if this rice husk waste can be used for preparation of valuable products. One of the application is its use as silica source in the synthesis of zeolites like ZSM-5, which are silico-aluminates. Rice husk waste is available in wide range of particle sizes in agricultural farms. There is no study available in open literature on use of these wide particle ranges for its direct application. This paper is an attempt to use wide particle size rice husk, its effect on ZSM-5 synthesis and its physico-chemical properties. Further these prepared ZSM-5 catalyst was evaluated for benzylation of mesitylene reaction. The study found that, rice husk of 600 mu m particle size is optimum as far as ZSM-5 synthesis, its physicochemical properties and further its application in mesitylene benzylation reaction.
Keywords: Mesitylene; Particle size; rice husk; Silica Source; ZSM-5

Comparative studies of the influence of particle size on various pretreatments of rice husk by assessment of chemical and structural components and wastewater characteristics of liquid fraction - Shahabazuddin, Mohmmad; Banuvalli, Bhavana Karibasappa; Mulik, Nagesh; Pande, Ashwini; Bokade, Vijay; Mudliar, Sandeep Narayan (Biomass Conversion and Biorefinery, 2023)
The dilute acid (DA), steam explosion (SE), and a 2-step: steam explosion followed by alkali (SEA) were evaluated for pretreatment of rice husk. The maximum hemicellulose and lignin removal via degradation and dissolution was observed for SEA pretreatment, enabling higher cellulose enrichment (up to 44% w/w) and recovery (up to 78%). The hemicellulose solubilization was >90% for all the pretreatments, while maximum lignin removal (up to 62%) was observed for SEA pretreatment. The particle size in the range of 0.3-0.6 mm enabled higher pretreatment efficiencies in terms of cellulose enrichment. The liquid fraction obtained after DA pretreatment indicated higher COD values (20800-24440 mg/L) as compared to SEA (7800-11400 mg/L) due to lower cellulose recoveries in DAP (54-68%). SEM analysis of the biomass indicated disrupted regions with multiple pores. FTIR analysis revealed cleavage of lignin side chains, and XRD analysis confirmed the increase in cellulose crystallinity post-pretreatment.
Keywords: Lignocellulosic crop residues; Liquid-waste characterization; Particle size; Rice husk biomass; Steam explosion pretreatment

Transient response to perturbations in flow synthesis of citrate capped gold nanoparticles - Bari, Atul H.; Shukla, Neerja; Gavriilidis, Asterios; Kulkarni, Amol A. (Biochemical Engineering Journal, 2023)
This work reports the transient behavior of continuous flow synthesis of gold nanoparticles (Au NPs) when subjected to perturbations in operating conditions using controlled experiments. The intricacies are captured through a detailed mathematical model. Reversed Turkevich protocol was used for synthesis of Au NPs. The synthesis was first studied in batch mode to investigate the reaction kinetics and reproducibility of the process. The optimal set of operating conditions viz., residence time, flow rate, temperature was then used for flow synthesis in a 2 m, 1/16 & DPRIME;Polytetrafluoroethylene (PTFE) reactor with micromixer. Reactor clogging was avoided by using segmented flow. Inline UV measurement was used for real time monitoring of the process. Transient experiments were performed by abruptly changing the operating conditions. A mathematical model was found to be accurate in predicting the transient behavior of the exit precursor concentration and the particle size for unsteady state synthesis. Even a small change in process variables for short duration was found to disturb the quality of Au NPs for a significantly longer duration. Of the three operating parameters, the effect of temperature variation was seen to have a prolonged effect where the system remained in unsteady state for long time.
Keywords: continuous flow synthesis; gold nanoparticles; Particle size; segmented flow; Unsteady behavior